2017
DOI: 10.1080/21592799.2017.1335270
|View full text |Cite
|
Sign up to set email alerts
|

Ypt4andlvs1regulate vacuolar size and function inSchizosaccharomyces pombe

Abstract: The yeast vacuole plays key roles in cellular stress responses. Here, we show that deletion of lvs1, the fission yeast homolog of the Chediak-Higashi Syndrome CHS1/LYST gene, increases vacuolar size, similar to deletion of the Rab4 homolog ypt4. Overexpression of lvs1-YFP rescued vacuolar size in ypt4Δ cells, but ypt4-YFP did not rescue lvs1Δ, suggesting that lvs1 may act downstream of ypt4. Vacuoles were capable of hypotonic shock-induced fusion and recovery in both ypt4Δ and lvs1Δ cells, although recovery ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Herein, we have demonstrated that Rab4A is a modulator of endocytic volume because Rab4A overexpression leads to increased endosomal size in both MCF10A and MDA-MB-231, whereas knockdown of Rab4A results in increased endosomal size in MCF10A but not in MDA-MB-231 cells. Previously, similar results have been shown in other cell types (59)(60)(61), suggesting that precise control of Rab4 expression regulates EE volume in a cell-specific manner. Considering that Rab4 has been shown to be involved in both membrane fusion and fission events (58,62), changes in Rab4 expression could result in increased EE size.…”
Section: Discussionsupporting
confidence: 82%
“…Herein, we have demonstrated that Rab4A is a modulator of endocytic volume because Rab4A overexpression leads to increased endosomal size in both MCF10A and MDA-MB-231, whereas knockdown of Rab4A results in increased endosomal size in MCF10A but not in MDA-MB-231 cells. Previously, similar results have been shown in other cell types (59)(60)(61), suggesting that precise control of Rab4 expression regulates EE volume in a cell-specific manner. Considering that Rab4 has been shown to be involved in both membrane fusion and fission events (58,62), changes in Rab4 expression could result in increased EE size.…”
Section: Discussionsupporting
confidence: 82%
“…Here, we find that Ypt52 has an exclusive function in binding Bph1. Ypt52 might be equivalent to the Rab4 homolog Ypt4 in S. pombe, as deletions in the LYST homolog Lvs1 and Ypt4 lead to similar phenotypes (Rains et al, 2017). Bph1 is, however, more critical than Ypt52, because bph1Δ cells, but not ypt52Δ cells, sort Atg8 into the 9 vacuole lumen (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these studies have not found significant defects in the transport of biosynthetic proteins to lysosomes, nor in endocytosis. Similarly, loss of Lvs1, the LYST homolog in Schizosaccharomyces pombe, results in large vacuoles (Rains et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation